2019
DOI: 10.1101/725192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The evolution of paternal care: a role for microbes?

Abstract: 10Paternal care is an evolutionary mystery. Despite extensive research, both theoretical and 11 experimental, the reasons for its ubiquity remain unclear. Common explanations include kin 12 selection and limited accuracy in parentage assessment. However, these explanations do not 13 cover the breadth of circumstances in which paternal care has been observed, particularly in 14 cases of uncertain paternity. Here we propose that microbes may play a key role in the 15 evolution of paternal care among their hosts.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…The evolution of cooperative behaviors should consider the strength of selection, the heritability of the group and individual level traits, and the genetic correlation between them ( Goodnight, 2005 ). However, given different examples of adaptability provided by studies of symbiotic relationships with microorganisms ( Li et al, 2008 ; Ezenwa et al, 2012 ; Cani et al, 2019 ; Gurevich et al, 2020 ), it is highly unlikely that natural selection could be applying any selective mechanisms only to genotypes or phenotypes of individuals.…”
Section: Making Choices In a Social World: Conspecific And Microbial ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The evolution of cooperative behaviors should consider the strength of selection, the heritability of the group and individual level traits, and the genetic correlation between them ( Goodnight, 2005 ). However, given different examples of adaptability provided by studies of symbiotic relationships with microorganisms ( Li et al, 2008 ; Ezenwa et al, 2012 ; Cani et al, 2019 ; Gurevich et al, 2020 ), it is highly unlikely that natural selection could be applying any selective mechanisms only to genotypes or phenotypes of individuals.…”
Section: Making Choices In a Social World: Conspecific And Microbial ...mentioning
confidence: 99%
“…This implies, on the one hand, the understanding of the role that the microbiome could play in the evolution of social behavior. For now, mathematical models suggest that the microbiome is key to explain the evolution of complex social behaviors, such as altruism, cooperation, and parental care ( Lewin-Epstein et al, 2017 ; Gurevich et al, 2020 ; Lewin-Epstein and Hadany, 2020 ). On the other hand, several hosts forming a social group can modify their social microbiome, as well as microbial transmission routes ( Miller et al, 2018 ), by making shared or unshared decisions for accessing to resources (e.g., beneficial endosymbionts).…”
Section: Potential Biochemical and Molecular Mechanisms That Gut Bact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous models studied interactions between microbial strains within the microbiome [26][27][28] and also host-microbe interactions [29][30][31][32] . Here we combine these two approaches into a framework that models the eco-system of a host, whose wellbeing and behavior alters the microbiome composition, and the microbiome, which affects the host state.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed mechanisms by which the microbiome can affect its host behavior [15,16], including insects [17,18]. Other studies have explored the evolutionary perspective of microbiome-induced social interactions [19][20][21]. In the current controlled laboratory study we used the desert locust (Schistocerca gregaria) as a model with which we directly explore the association between solitary-togregarious phase transition and the individual locust's microbiome.…”
Section: Introductionmentioning
confidence: 99%